Prevalence rate of cytomegalovirus infection in individuals with and without systemic lupus erythematosus - Ferdowsi , Fatemeh; Haghigh, Anousheh; Barati, Mitra; Shirani, Fatemeh; Keyvani, Hossein; Naghdalipour, Mehri; Kianmehr, Nahid (Researcher Bulletin of Medical Sciences, 2020)
Background: The role of cytomegalovirus (CMV) infection in triggering or exacerbating systemic lupus erythematosus (SLE) remains a subject of debate. The aim of this study was to compare the prevalence rate of CMV infection between individuals with and without SLE. Materials and Methods: This cross-sectional comparative study recruited 52 consecutive patients with SLE (based on the criteria determined by the Systemic Lupus Collaborating Clinics, 2012) and 52 healthy subjects. The exclusion criteria were immunodeficiency and other background diseases. CMV infection was assessed according to serology (enzyme-linked immunosorbent assay) and polymerase chain reaction (PCR). Results: Immunoglobulin G (IgG) was positive in all participants. Immunoglobulin M (IgM) was positive in eight SLE patients (15.4%) and none of the controls (p = 0.003). The PCR was positive in four SLE patients (7.7%) and none of the controls (p = 0.041). IgM level was not related to age, gender, literacy, marital status, family history, SLE disease activity index (SLEDAI), or duration of the disease (p > 0.05). Conclusion: According to this study, CMV infection was higher in SLE patients but was not related to the type of organ involvement, type of immunosuppressive drug, or SLEDAI.